Modernization in the Islamic World: Between Westernization and Islamization in the Social, Political, and Thoughtful Dynamics of Muslims in the Contemporary Era - Yenny Juliana; Winengan Winengan; Abdul Malik (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the dynamics of modernization in the Islamic world by highlighting the interaction between westernization and Islamization that occurs in the social, political, and intellectual life of Muslims in the contemporary era. Modernization, on the one hand, brings positive impacts such as advancements in science, technology, and governance, yet on the other hand, it presents challenges through the shifting of values and orientations influenced by Western secularism and rationalism. This research employs a qualitative approach using library research methods, drawing data from accredited SINTA journals, academic books, and relevant literature on modernization and Islamic thought. The findings indicate that westernization and Islamization are not necessarily opposing forces; rather, they interact dynamically and adaptively in shaping modern Islamic identity. Islamization functions as a moral and spiritual response to the influence of Western modernity, emphasizing the importance of balancing rational progress with religious and ethical values. In conclusion, the future of Islamic civilization depends on the ability of Muslims to manage modernization wiselyembracing global progress without losing Islamic principlesand to develop a form of Islamic modernity that is civilized, ethical, and contextually relevant to the times.